Taxonomia de porífera do Arquipélago de São Pedro e São Paulo, Brasil - Moraes, Fernando Coreixas de (2002)
Despite its great biogeographic and strategic importance, only six sponge species have been identified from São Pedro and São Paulo Archipelago, Brazil (formerly Saint Paul Rocks ), since 1886. ln the present study 101 sponge specimens were collected in the archipelago through free diving and SCUBA down to 50 m depth in two expeditions in 2000 and 2001. Twenty-one species were described, including photographs of living and preserved specimens, light micrographs of thick sections, scanning electron micrographs of microscleres, and camera lucida drawings of megascleres. Seventeen species were identified at species level and four at genus level; they represent 10 orders of two classes of Porifera (Calcarea and Demospongiae ). Five new species and 20 new records for the archipelago are described. The genus Discodermia, known to produce compounds with high pharmacological potential is recorded for the first time from Brazil. A key to the identification of the 21 species described is given. Based on previous records, field observations and present identifications, I estimate that 29 is the minimum number of sponge species in São Pedro and São Paulo Archipelago. The sponge fauna of the archipelago has greater similarity with those of Brazil and Caribbean than with that of West Africa, supporting the hypothesis of its colonization via the Equatorial Counter-Current.